Wellbeing After a Managed Retreat: Observations from a Large New Zealand Program - Thoa Hoang; Ilan Noy (Center for Economic Studies and ifo Institute (CESifo), 2019)
Managed retreat programs aim to relocate households or remove homes and other infrastructure out of harm's way. Managed retreats are most typically considered for coastal areas or floodprone zones. In New Zealand, as elsewhere, managed retreat initiatives generate a highly polemical and emotional discussion within affected communities, and between them and the government. Given the difficult and controversial implementation of managed retreats, understanding what happens to residents who are displaced by these programmes is of immense importance. We examine the wellbeing of the people who were forced to move as part of a large managed-retreat program that was implemented in Christchurch, New Zealand, after the 2011 earthquake the city experienced. We consider three indicators for the measurement of subjective (surveyed) wellbeing: quality of life, stress, and emotional wellbeing. Our aims are: (1) to describe the wellbeing of the relocated residents after they were forced to move, and identify which factors are correlated with their well-being having already moved to new places (2) to describe the subjective experience of the residents in their communication with the government and in their relation with the community: (3) to identify the effect of economic factors (household annual income, home ownership, and financial impacts) on their wellbeing; and (4) to relate these findings to possible lessons for policy makers when designing managed retreat programs.
Keywords: Q54; 330; managed retreat; wellbeing; shock; relocation; climate change